Low Levels of MicroRNA‐21 Are a Marker of Reduced Arterial Stiffness in Well‐Controlled Hypertension. Issue 3 (22nd August 2016) - Parthenakis, Fragiskos; Marketou, Maria; Kontaraki, Joanna; Patrianakos, Alexandros; Nakou, Helen; Touloupaki, Maria; Vernardos, Michail; Kochiadakis, George; Chlouverakis, Gregory; Vardas, Panos
Abstract : MicroRNAs (miRNAs) play a crucial role in myocardial and vascular remodeling and have emerged as potential diagnostic and prognostic biomarkers or as therapeutic targets. The authors aimed to investigate the expression profile of selected miRNAs in the peripheral blood of patients with well‐controlled essential hypertension in relation to arterial stiffness. Expression levels of miRNAs miRNA‐1, miRNA‐133a, miRNA‐26b, miRNA‐208b, miRNA‐499, and miRNA‐21 in peripheral blood mononuclear cells were quantified by real‐time reverse transcription polymerase chain reaction. Carotid‐femoral pulse wave velocity (cfPWV) and carotid radial pulse wave velocity (crPWV) were evaluated at baseline and after 1 year of effective antihypertensive therapy. A total of 95 patients (50 men, mean age 62±9 years) with well‐controlled essential hypertension were included in the analysis. Only miRNA‐21 was independently correlated with changes in both cfPWV and crPWV, independently of blood pressure levels ( r =−0.56 and r =−0.46, respectively; P <.001 for both). Low levels of miRNA‐21 are strongly associated with an improvement in arterial stiffness in patients with well‐controlled essential hypertension, independently of their blood pressure levels. These data highlight the significance of miRNA‐21 in vascular remodeling and its role as a potential prognostic marker and future therapeutic target.